Pergeseran Otoritas Keagamaan Di Era Media Sosial: Tantangan Otentisitas Tafsir Dalam Konten Digital - Syaiful Aslam (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2025)
Before the digital age, religious authority came from formal institutions such as Islamic boarding schools and seminaries. The legitimacy of scholars and religious leaders is obtained through systematic education and affiliation with established institutions. However, social media has disrupted traditional religious authority. Platforms like YouTube and TikTok are becoming new spaces for religious content without institutional filters. The shift in religious authority has an impact on the authenticity of interpretation in digital content. This study aims to see how the dynamics of religious authority shift and how the challenges of interpretation authenticity in the digitalization era are as well as how to maintain the authenticity of interpretation in the digital era. The approach used is a qualitative approach with the Literature study method. The results obtained indicate that there is a shift in religious authority, from traditional to conventional. then there are three challenges to the authenticity of interpretation in digital content, namely: data validity and reliability of digital sources, content simplification, content manipulation and disinformation. And the efforts to maintain authenticity are Digital Education and Literacy, the Role of Ulema and Religious Institutions, Collaboration with Digital Platforms.